Determinação da heterose e da capacidade geral e específica de combinação para dez características agronômicas em pimentão (Capsicum annuum L.) - MESQUITA, Júlio Carlos Polimeni de (2008)
The aim of the present study was to evaluate the agronomic potential, general and specific capability to combine and heterosis between the varieties of sweet pepper (Capsicum annuum L.). The experiments were conducted at the Crop Area of the Agronomy Department of the Federal Rural University of Pernambuco in Recife, Pernambuco (Brazil) (latitude 8° 10'52''S and longitude 34° 54'47''W) from December 27, 2007 to May 9, 2008. There was partial diallel cross balanced between four varieties (HTV-1, HTV-2, HTV and HTV-3-4), resulting in six F1 hybrids without the reciprocal. The four strains used as parents and the six hybrids from the diallel were planted in polystyrene trays; 30 days after sowing, the plants were transplanted into 5-L plastic pots containing powdered coconut as substrate and fertirrigated daily with a nutritive solution. We evaluated the overall capability (GCC) and specific capability (SCC) of the combination of the four varieties and six hybrids, with differences found in GCC and SCC in December regarding the following agronomic characteristics: total number of fruits; number of the fruits from early production;early production weight; total weight of fruit; average weight of fruit; average fruit length; average fruit diameter;length/diameter ratio (C/D); average thickness of the pericarp; and average number of locules. According to GCC estimates (gi), HTV-2 and HTV-4 varieties achieved positive values for early production weight and the strain HTV-2 also achieved positive values for total weight of fruits. The SCC revealed that the hybrid combinations with positive values of heterosis were HTV-1 x HTV-2 and HTV-3 x HTV-4 for seven of the ten characteristics evaluated, followed by HTV-2 x HTV-3, which received positive values for total weight of the fruit, average fruit weight and average fruit diameter. Systems of diallel crosses are important for evaluating alternative genotypes as well as indicating the best hybrids and choosing the most promising parents for use in hybridization programs. Another experiment was conducted using the HTV-1, HTV-2, HTV-3, HTV-4, HTV-5, HTV and HTV-6-7 varieties, fifteen experimental hybrids (HTV-1 x HTV-2 , HTV-1 x HTV-3, HTV-1 x HTV-4, HTV-2 x HTV-3, HTV-2 x HTV-4, HTV-3 x HTV-4, HTV-5 x HTV-2, HTV -6 X HTV-2, HTV-5 x HTV-3, HTV-6 x HTV-3, HTV-2 x HTV-7, HTV-3 x HTV-7, HTV-5 x HTV -4, HTV-6 x HTV-4 and HTV-7 x HTV-4), an open-pollinated cultivar ("All Big") and a commercial hybrid("Atlantis"), which were evaluated in a hydroponic production system of a greenhousein order to identify the seven most promising strains for inclusion in breeding programs as well as study the effects of heterosis in 16 experimental hybrids (F1) regarding the mean of the parents, mean of the superior parent, a standard cultivar (All Big) and a standard hybrid (Atlantis F1) for December, addressing ten agronomic characteristics. The ratio between the coefficient of genetic variation and the coefficient of environmental variation (CVg/CVe) achieved values greater than 1.0 for all characteristics studied. For the heterosis, the most expressive values were found for the characteristics of early production and total weight of fruits. The hybrids HTV-2 x HTV-3, HTV-2 x HTV-4, HTV-5 x HTV-2, HTV-6 x HTV-2, HTV-2 x HTV-7 and HTV-6 x HTV-4 achieved positive heterosis values regarding early production in relation to the mean of the parents, the parent with the larger mean, the standard cultivar and the standard hybrid. The HTV-5 x HTV-2, HTV-2 x HTV-7 treatments achieved positive heterosis values regarding weight of the fruit in relation to the standard hybrid. The hybrid HTV-2 x HTV-7 was found to have potential for use in field evaluations in order to test its superiority. The presence and magnitude of heterosis demonstrate theprospect for the production of hybrids. Knowledge on the behavior of the F1 hybrids in relation to their cultivar parents allows the selection of the best genetic combinations for the desired characteristic.